Development of a Mobile-based Application for RJ Studio's Administration and Booking using an object-oriented approach - Murugan, Divya; Mohd Zin, Nur Ariffin (Applied Information Technology And Computer Science, 2023)
RJ Charter is a mobile application designed to address the challenges faced by RJ Studio, a photography studio, in managing bookings and enhancing customer convenience. With a lack of a proper booking system, customers struggle to check the studio's availability, while the management team faces difficulties in organizing and managing bookings effectively. RJ Charter aims to resolve these issues by providing a user-friendly interface for customers to easily book available slots. Through features like a booking system and administration system, the application streamlines the management of bookings, providing real-time updates on schedules. Developed using Android Studio, Laravel, and Dart programming language, RJ Charter enables customers to book photography sessions, reserve studio time, and place printing service orders, eliminating the need for physical visits or phone calls. By enhancing operational efficiency and offering a seamless experience, RJ Charter aims to transform the way customers interact with RJ Studio and simplify booking management.